Molybdenum - Fairweather-Tait, Susan (Henry Stewart Talks, 2025)
Molybdenum function in the body, Food sources of Molybdenum, Metabolism and absorption of Molybdenum in the body, Molybdenum toxicity, Dietary reference values for Molybdenum in adults